Allometric growth in the fiddler crab Uca thayeri (Brachyura, Ocypodidae) from a subtropical mangrove - Negreiros-Fransozo, M. L.; Colpo, K. D.; Costa, T. M. (Crustacean Soc, 2003)
The relative growth of U. thayeri was studied for a subtropical mangrove population in the estuary of the Comprido and Escuro rivers, Ubatuba, São Paulo State, Brazil. The evaluation of the morphological sexual maturity of U. thayeri was performed using the allometric technique. Remarkable ontogenetic changes were observed in the allometric growth of the male major cheliped and the female abdomen, indicating that these structures are closely connected to the timing of sexual maturity. For males, the relative-growth analysis of cheliped propodus length rendered an estimate of 13.8 mm of carapace width for the size at onset of sexual maturity. A distinct growth pattern was observed for the abdomen of U. thayeri females. It has a wide puberty size range (from 10.7 to 16.8 mm of CW) compared to other brachyurans previously studied. Thus, the females' abdominal growth can be represented by three growth phases: immature, transitional, and mature. The major cheliped is the fight one in 50% of males. The median length of the male major cheliped did not differ between right- and left-handed crabs.